Improvement of damping properties of structural member using soft material at support - Kodavanla, Babitha; A. Barai, Dr; B. S. Dadapeer, A; Threza, Mery; Hanuma, P; Madhavi, N (International Journal of Engineering and Technology, 2018)
Coincidental plane vibration in the midst of flight isn't unusual. There are different purposes behind plane vibration, including landing gear increase and withdrawal, extension of speed brakes, free play in versatile surfaces, and breakdowns of frameworks. Air vehicles have an airframe structure which incorporates every single auxiliary part. This task manages Improvement of damping properties of the basic part utilizing a delicate material at the help. So in this task considered a cantilever auxiliary part made up of composite and aluminum materials and delicate material is elastic, settling for support. How the damping properties are changing in basic part with and without delicate material, and discover which structure is having higher damping properties. Consequently, the objective of the present work is to demonstrate that the damping will enhance when the delicate material utilized at the help and composite has higher damping than aluminum.Â